Transformation of Learning in The 4.0 Era through Educational Technology and Its Implications for Ethical Humanistic Religious Values - Silmi Khoiria Syahida; Istanto Istanto (Universitas Muhammadiyah Surakarta, 2025)
This study analyzes the transformation of learning in the Industry 4.0 era through digital technology and its implications for ethical, humanistic, and religious values. Using a qualitative conceptual approach and literature review, data were collected from books, journals, and scientific articles on digital learning, educational ethics, and moral-spiritual development. Analysis was conducted descriptively and critically to explore the relationship between digital practices and student character formation. Results indicate a shift from teacher centered to learner-centered learning, with digital technology supporting active engagement, collaboration, and critical thinking. Integrating ethical, humanistic, and religious values helps students understand the moral and social consequences of their actions, enhancing integrity, empathy, social responsibility, and spiritual awareness. The study highlights the importance of balanced digital learning strategies that strengthen both technical competencies and character development, providing guidance for educators and policymakers to design adaptive, inclusive, and character-building learning in the digital era.